Development and production of Cantaloupe melon as a function of plant spacing and growing environments in the Brazilian Cerrado - Vendruscolo, Eduardo Pradi; Seleguini, Alexsander; Campos, Luiz Fernandes Cardoso; Rodrigues, Aliny Heloísa Alcântara; de Lima, Sebastião Ferreira (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Melon is responsive to the cultivation environment and the production techniques that are used, factors crucial for obtaining high quality fruits. The objective of this research was to study the vegetative growth, productive potential and quality of Cantaloupe melon fruits as a function of a reduction of spacing in two growing environments. Using a randomized block design, melon plants (cv. Trinity) were cultivated in an open field and a protected environment, with five different spacing between plants (15, 25, 35, 45 and 55 cm). It was observed that the plant growth rates, leaf emission rate, thickness of bark and pulp, total soluble solids content, and ratio were higher with the protected cultivation. For spacing, the increase influenced, in a linear and positive manner, the characteristics of dry mass of plants, fresh mass of fruits and thickness of the pulp. However, increasing the plant density increased productivity. For growth velocity, foliar emission velocity and fruit length and circumference, maximum points were observed when the plants were spaced at 47.50, 53.75, 49.95 and 47.51 cm from each other, respectively. Considering these results, for regions with similar conditions to the present study, the cultivation of the Cantaloupe melon is favored when conducted under protected cultivation conditions, with a plant spacing between 45 and 55 cm.